2006
DOI: 10.1179/174328606x98321
|View full text |Cite
|
Sign up to set email alerts
|

Labour productivity model (WPMR system) and its application to the stripping area of Garp Lignite Enterprise in Turkey

Abstract: Although labour productivity problems are thought of as a factor mainly caused by the lack of commitment by the labour force, it essentially arises by a process in which several parameters are interrelated such as the effects of legislation, management and labour responsibility. In the present study, the method of Labour Productivity Management by Ratio (WPMR) was used to assess labour productivity at the lignite mining company, GLE-Turkey, since this method takes into account the factors affecting labour prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In 2013 Akçakoca et al used WPMR system to evaluate the labor productivity in Turkey. The conclusion of this study was that labor productivity was found to be lower than should be expected (Akçakoca et al, 2006). In a study conducted by Uçmuş and Kaçar in 2015 at a congress about productivity, labor productivity was investigated in a battery company.…”
Section: Introductionmentioning
confidence: 80%
“…In 2013 Akçakoca et al used WPMR system to evaluate the labor productivity in Turkey. The conclusion of this study was that labor productivity was found to be lower than should be expected (Akçakoca et al, 2006). In a study conducted by Uçmuş and Kaçar in 2015 at a congress about productivity, labor productivity was investigated in a battery company.…”
Section: Introductionmentioning
confidence: 80%
“…Labour productivity: Manpower employment and mining outputs are related with labour productivity (Akçakoca et al, 2006;Tilton and Landsberg, 1999). Labour invested, non-labour operating expenditures (Lala et al, 2016) etc all have an impact on labour productivity.…”
Section: Human Resource Issuesmentioning
confidence: 99%
“…are some of the requirements essential in modern mining. Quality deterioration of workforce (Bradley and Sharpe, 2009) and inadequate training (Akçakoca et al, 2006) works against the company's progress.…”
Section: Political Influencementioning
confidence: 99%
See 2 more Smart Citations